2017
DOI: 10.3390/dj5010004
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing the Risk Factors of Severe Early Childhood Caries

Abstract: Severe early childhood caries remains the most common chronic disease affecting children. The multifactorial etiology of caries has established a controversy about which risk factors were more significant to its development. Therefore, our study aimed through meticulous statistical analysis to arrange the “well agreed upon” common risk factors in order of significance, to aid the clinician in tailoring an adequate preventive program. The study prioritized or reshuffled the risk factors contributing to severe e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
19
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 27 publications
7
19
1
1
Order By: Relevance
“…The age range of 12-36 months was chosen to expose the primary dentition to the oral environment for a minimum period of 6 months post-eruption. In the present study, the gender distribution of ECC among boys and girls was found to be equal which was in contrast to studies conducted by Maciel et al and Kabil et al who reported a higher prevalence in boys compared to girls, with highly significant results (p < 0.001) [17][18].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The age range of 12-36 months was chosen to expose the primary dentition to the oral environment for a minimum period of 6 months post-eruption. In the present study, the gender distribution of ECC among boys and girls was found to be equal which was in contrast to studies conducted by Maciel et al and Kabil et al who reported a higher prevalence in boys compared to girls, with highly significant results (p < 0.001) [17][18].…”
Section: Discussioncontrasting
confidence: 99%
“…The inverse relation between SES and ECC reported in the current study was similar to other studies by Tyagi et al , Plutzer et al and Kabil et al that ascribed the unawareness regarding oral health care for children of parents with low socio-economic groups to this finding [18][19][20]. Delay in dental visits and inconsideration of oral health as a priority could be other possible reasons.…”
Section: Discussionsupporting
confidence: 92%
“…It is also worth mentioning that according to data extracted from Egypt's national oral health survey, Egyptian boys were more liable to suffer from ECC than girls and this goes in line with the findings of another cross sectional study conducted in Cairo governorate. [30] In addition, similar gender disparities in caries experience have been observed in other populations and among both children and adults. [31] A plausible explanation is that usually girls are more inclined to comply with instructions including health messages and in one study it was found that, when instructed, they brushed their teeth more frequently than boys.…”
Section: Discussionmentioning
confidence: 71%
“…The main risk factors of severs early childhood caries (S-ECC) were identified as following: the level of education of fathers and /or mothers, child's dietary habits, oral hygiene practice in addition to child dental visits can (24) .…”
Section: Introductionmentioning
confidence: 99%